2020
DOI: 10.3390/ijerph17228367
|View full text |Cite
|
Sign up to set email alerts
|

Role of qSOFA and SOFA Scoring Systems for Predicting In-Hospital Risk of Deterioration in the Emergency Department

Abstract: The objective of this study was to analyze and compare the usefulness of quick sequential organ failure assessment score (qSOFA) and sequential organ failure assessment (SOFA) scores for the detection of early (two-day) mortality in patients transported by emergency medical services (EMSs) to the emergency department (ED) (infectious and non-infectious). We performed a multicentric, prospective and blinded end-point study in adults transported with high priority by ambulance from the scene to the ED with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 38 publications
(59 reference statements)
1
5
0
Order By: Relevance
“…In this line, two studies by Koch et al 16 and Loonen et al 17 evaluated diagnostic accuracy of suPAR have shown specificity from 64–77%. Also, the current findings agreed with the study by López-Izquierdo et al 18 found that for 28-day mortality, the qSOFA presented a cut-off of two points, with a sensitivity of 74.3 and specificity of 73.1. The SOFA score presented a cut-off of three points for 30-day mortality, with a sensitivity of 81.6 and a specificity of 76.5.…”
Section: Discussionsupporting
confidence: 93%
“…In this line, two studies by Koch et al 16 and Loonen et al 17 evaluated diagnostic accuracy of suPAR have shown specificity from 64–77%. Also, the current findings agreed with the study by López-Izquierdo et al 18 found that for 28-day mortality, the qSOFA presented a cut-off of two points, with a sensitivity of 74.3 and specificity of 73.1. The SOFA score presented a cut-off of three points for 30-day mortality, with a sensitivity of 81.6 and a specificity of 76.5.…”
Section: Discussionsupporting
confidence: 93%
“…AUROC for the SOFA was in our study lower than in prior studies (Table 4). 9,[11][12][13][14]19,[21][22][23][24][25] The different findings can be explained by differences in methodology. Several studies 9,11,12,22,23 have used the worst values of variables from the ED stay to calculate SOFA.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it proves that although respondents do not know the updated definition of sepsis based on the Sepsis-3 guidelines, respondents know the qSOFA indicators as clinical criteria for sepsis. Furthermore, López-Izquierdo et al (2020) also stated in their research that the qSOFA score could be used as an initial assessment to detect patients at high risk of sepsis [34]. Thus, it is expected that knowing the clinical criteria for sepsis based on qSOFA respondents can have good behavior in the early detection of sepsis.…”
Section: Discussionmentioning
confidence: 99%